2002
DOI: 10.1126/science.296.5576.2193
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Source of Bose-Einstein Condensed Atoms

Abstract: A continuous source of Bose-Einstein condensed sodium atoms was created by periodically replenishing a condensate held in an optical dipole trap with new condensates delivered using optical tweezers. The source contained more than 1 x 10(6) atoms at all times, raising the possibility of realizing a continuous atom laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 19 publications
3
134
0
Order By: Relevance
“…In accordance with a recent experiment [13], we found that it is possible to create a single condensate with larger condensate fraction and a unique zero relative phase between the initial condensate modes. By examining the energy spectrum of the Hamiltonian under the two-mode approximation, the process can be understood both within and without the adiabatic limit.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In accordance with a recent experiment [13], we found that it is possible to create a single condensate with larger condensate fraction and a unique zero relative phase between the initial condensate modes. By examining the energy spectrum of the Hamiltonian under the two-mode approximation, the process can be understood both within and without the adiabatic limit.…”
Section: Discussionsupporting
confidence: 92%
“…Experimentally, for the cigar-shaped condensates, it is much better to merge them along the radial direction [13]. The reason is that we have assumed that the density profile of the atoms can adiabatically follow the movements of the traps to validate the two-mode model.…”
Section: Comparison Of Different Merging Methodsmentioning
confidence: 99%
See 3 more Smart Citations